Patient-Reported Outcome Measures in Upper Airway–Related Dyspnea: A Systematic Review - Noud, Meaghan (JAMA Otolaryngol Head Neck Surg, 2017)
IMPORTANCE: Patient-reported outcome (PRO) measures address the need for patient-centered data and are now used in diverse clinical, research, and policy pursuits. They are important in conditions causing upper airway–related dyspnea in which the patient’s reported experience and physiological data can be discrepant. OBJECTIVES: To perform a systematic review of the literature on upper airway dyspnea–related PRO measures and to rigorously evaluate each measure’s developmental properties, validation, and applicability. EVIDENCE REVIEW: This study strictly adhered to Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines. MEDLINE via the PubMed interface, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), and the Health and Psychosocial Instruments (HaPI) database were searched using relevant vocabulary terms and key terms related to PRO measures and upper airway–related dyspnea. Three investigators performed abstract review, and 2 investigators independently performed full-text review by applying an established checklist to evaluate the conceptual model, content validity, reliability, construct validity, scoring and interpretability, and respondent burden and presentation of each identified instrument. The initial literature search was conducted in November 2014 and was updated in April 2016. FINDINGS: Of 1269 studies reviewed, 3 upper airway–related dyspnea PRO measures met criteria for inclusion. One PRO measure was designed de novo to assess upper airway–related dyspnea symptoms and monitor treatment outcomes, while 2 were adapted from established instruments designed for lower airway disease. Measurement properties and psychometric characteristics differed, and none met all checklist criteria. Two met a criterion in each of 7 domains evaluated. Two demonstrated test-retest and internal consistency reliability, and 2 showed that their scores were responsive to change. Thematic deficiencies in current upper airway–related dyspnea PRO measures are lack of patient involvement in item development (content validity), plan for interpretation, and literacy level assessments. CONCLUSIONS AND RELEVANCE: PRO measures are critical in the assessment of patients with upper airway–related dyspnea. Three instruments with disparate developmental rigor have been designed or adapted to assess this construct. Care must be taken to understand the measurement characteristics and contextual relevance before applying these PRO measures for clinical, research, or quality initiatives.